A process for producing polystyrene-acrylonitrile. - Tan, Wee Tee; Radhi, Muhammed Mizher; Ab. Rahman, Mohamad Zaki; Kassim, Anuar (2010)

(untitled)
The present invention relates to a process for producing polystyrene-acrylonitrile, wherein the process involves the steps of irradiating a mixture containing a constant amount of a polymer, a monomer having a concentration of between 50 to 90% and ferrous ammonium sulfate (FAS) having a concentration of between 0.25 to 2% wherein the step of irradiating the mixture is conducted via a gamma-irradiation having a dose of between 0.4 to 1.5 Mrad.